Carbon Nanotube as a Tool for Fighting Cancer - Comparetti, Edson José [UNESP]; Pedrosa, Valber De Albuquerque [UNESP]; Kaneno, Ramon [UNESP] (American Chemical Society (ACS), 2018)
In 2015, cancer was the cause of almost 22% of deaths worldwide. The high frequency of relapsing diseases and metastasis requires the development of new diagnostic and therapeutic approaches, and the use of nanomaterials is a promising tool for fighting cancer. Among the more extensively studied nanomaterials are carbon nanotubes (CNTs), synthesized as graphene sheets, whose spiral shape is varied in length and thickness. Their physicochemical features, such as the resistance to tension, and thermal and electrical conductivity, allow their application in several fields. In this review, we show evidence supporting the applicability of CNTs in biomedical practice as nanocarriers for drugs and immunomodulatory material, emphasizing their potential for use in cancer treatment.